Mushārakah Mutanāqiṣah (Diminishing Partnership) Regulation for Housing Finance in Indonesian and Malaysian Law - Asyiqin, Istianah Zainal; Akbar, M. Fabian; Onielda, Muhammad Daffa Auliarizky; Farid, Adriana Maisarah binti Mohd (Al-Ahkam, 2024)
The housing business continues to grow along with the increasing need for the fulfillment of housing. This research delves into the application of mushārakah mutanāqiṣah in housing finance within Indonesia and Malaysia, scrutinizing their regulations and relevant governing institutions. Employing a normative legal approach, it explores legal principles, systematics, synchronization, and historical context about this financing method. Employing inductive, deductive, and comparative methods, it analyzes regulations and practices in both countries. By offering insights into the potential and challenges of implementing mushārakah mutanāqiṣah in housing finance, the study aims to provide recommendations for regulatory enhancements, fatwa institutions, product development, and adherence to sharī’ah principles. This research is crucial for deepening understanding and facilitating improvements in various sectors related to housing finance within the context of Islamic finance in Indonesia and Malaysia.